TWEAK/Fn14 mediates atrial‐derived HL‐1 myocytes hypertrophy via JAK2/STAT3 signalling pathway. Issue 9 (4th July 2018) - Hao, Li; Ren, Manyi; Rong, Bing; Xie, Fei; Lin, Ming‐jie; Zhao, Ya‐chao; Yue, Xin; Han, Wen‐qiang; Zhong, Jing‐quan
Abstract: Atrial myocyte hypertrophy is one of the most important substrates in the development of atrial fibrillation (AF). The TWEAK/Fn14 axis is a positive regulator of cardiac hypertrophy in cardiomyopathy. This study therefore investigated the effects of Fn14 on atrial hypertrophy and underlying cellular mechanisms using HL‐1 atrial myocytes. In patients with AF, Fn14 protein levels were higher in atrial myocytes from atrial appendages, and expression of TWEAK was increased in peripheral blood mononuclear cells, while TWEAK serum levels were decreased. In vitro, Fn14 expression was up‐regulated in response to TWEAK treatment in HL‐1 atrial myocytes. TWEAK increased the expression of ANP and Troponin T, and Fn14 knockdown counteracted the effect. Inhibition of JAK2, STAT3 by specific siRNA attenuated TWEAK‐induced HL‐1 atrial myocytes hypertrophy. In conclusion, TWEAK/Fn14 axis mediates HL‐1 atrial myocytes hypertrophy partly through activation of the JAK2/STAT3 pathway.